Green Synthesis and Characterization of Gold Nanoparticles Using Tamarindus indica Seed Gum Via Microwave Synthesis - Amrutham Santoshi Kumari; Venkatesham Maragoni (Chemical and Materials Sciences: Developments and Innovations Vol. 7, 2024)
The initiation of production of huge advanced nanotechnology encourages the usage of noble metal-based Nanoparticles (NPs) for the diagnosis of diseases, selected drug delivery, biological treatment of cancerous cells, and bioimaging. Recent work has established a well-systemized focus on the synthesis, capping, stabilizing and characterization of gold nanoparticles. In this study, tamarind seed gum as a capping and stabilizing agent was used for gold nanoparticles. Auric Chloride Trihydrate (AuCl3·3H2O), Rhodamine 6G, and Tamarind seed gum (extracted from the seeds of the Tamarind tree) were collected from the Sree Dattha Group of Institutions, Sheriguda, Telangana, India. AuNPTSG were confirmed by UV, IR, XRD and TEM spectral studies. The UV-Visiblespectra revealed that there is a 525 nm absorption band conformation of Au nanoparticles. The particle size dispersal curve reveals that nanoparticles obtained are polydispersed in nature, having an average diameter of 12 nm. An innovative viable little cost methodology was used to synthesize the AuNPTSG. AuNPTSG was produced by the use of naturally occurring tamarind seed gum which acts as both as reducing and stabilizing agent. Water was used as an ecologically safe solvent.